2000
DOI: 10.1103/physrevc.61.025204
|View full text |Cite
|
Sign up to set email alerts
|

Electroproduction of strangeness above the resonance region

Abstract: A simple and elegant model, based on Reggeized t-channel exchanges is succesful in reproducing the main features of all existing data of the reactions ep->eKLambda and ep->eKSigma. In particular, the original way gauge invariance is taken into account is found to be essential to describe the ratio between the Coulomb and the Transverse cross-sections at large Q2 that has been measured recently at JLab.Comment: 5 pages, 5 figures, submitted to Phys.Rev.Let

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 17 publications
(45 reference statements)
6
118
0
3
Order By: Relevance
“…A few years ago, Regge theory has experienced a renewed interest in the field of meson production after reports of Regge based models that accurately describe the high energy data [16,38,39,79]. Triggered by these observations, in this chapter we will explore the possibility of using Regge theory to account for the global behavior of the p(γ, K)Y and p(e, e K)Y data in the resonance region and beyond.…”
Section: Kς Electroproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few years ago, Regge theory has experienced a renewed interest in the field of meson production after reports of Regge based models that accurately describe the high energy data [16,38,39,79]. Triggered by these observations, in this chapter we will explore the possibility of using Regge theory to account for the global behavior of the p(γ, K)Y and p(e, e K)Y data in the resonance region and beyond.…”
Section: Kς Electroproductionmentioning
confidence: 99%
“…In the literature , only a limited number of theoretical studies on the p(e, e K)Y reaction can be found [11,13,38,39,64,65]. Most of those studies are based on isobar models which try to account for the photo and electroproduction data simultaneously.…”
Section: Strangeness Electroproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They published ep → enπ + cross sections with transverse-longitudinal separation, at Q 2 = 1.60 and 2.45 GeV 2 [14] and Q 2 = 2.15 and 3.90 GeV 2 [15], in the valence region (x Bj 0.3), and above the resonance region (W > 2 GeV). As we evoked in sub-section 5.2.1, Regge based models such as VGL [19,20,18] describe really well the longitudinal cross section. In contrast with this, the Regge predictions given by the previously cited models disagree by more than one order of magnitude with the measured transverse cross section, and this disagreement increases with Q 2 .…”
Section: Interpretation Within Semi-inclusive Frameworkmentioning
confidence: 99%
“…1.5 for our example) with the propagator of a trajectory (see [19,20] for recent sources). The trajectory propagator for a scalar S, or a pseudoscalar P S such as the π + is:…”
Section: Diagrams (mentioning
confidence: 99%